Konstantin Ushinsky’s world pedagogical heritage in the context of humanitarization in education - Abakumova, Natalia N.; Tsiguleva, Olesya V.; Ju, Chuanya; Lei, Guofang (Вестник Томского государственного университета)
The article presents a comparative analysis of methodological approaches to Konstantin Ushinsky’s pedagogical heritage in different countries. The authors examine literature, strategic and regulatory documents on organizing the educational process in Russian, Chinese, German and American universities in order to determine the humanitarian component of Ushinsky’s heritage. They describe differences in the interpretation of the concept “humanization in higher education” in the studies of scientists from Germany and the USA. They conclude about the unity of interpretations of the concept in Russian and Chinese practices.